1993
DOI: 10.1016/0014-5793(93)80857-q
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of the chicken annexin V gene and its correlation with the tertiary structure of the protein

Abstract: Chicken annexin V (anchorin CII) is a collagen binding, membrane-associated molecule with Ca" channel activity. Here we report on the coding sequences, promotor region, size and distribution of exons, and exon-intron junctions of the chicken annexin V gene. It is about 25 kb long and codes for 13 short exons between 50 and 581 bp length. Exon sizes and locations of splice sites are almost completely homologous to those of the human and mouse annexin II or pigeon annexin I genes, although there is only SO-60% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Mouse and rat annexin A5 genes present two promoter regions; different transcripts and alternatively spliced mRNA species have been detected [Imai and Kohsaka, 1995;Rodrõ Âguez-Garcõ Âa et al, 1999]. However, we have only detected a unique transcript for chicken annexin A5; moreover, the analysis of its gene revealed only one promoter and the absence of TATA boxes and other cis-regulatory elements [Pfannmu È ller et al, 1993;Ferna Ândez et al, 1994], suggesting that the annexin A5 gene might be more related to that of a housekeeping gene. Here we show for the ®rst time that at least two regulatory mechanisms exist which control annexin A5 expression in a developmental and an environmentally regulated manner.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Mouse and rat annexin A5 genes present two promoter regions; different transcripts and alternatively spliced mRNA species have been detected [Imai and Kohsaka, 1995;Rodrõ Âguez-Garcõ Âa et al, 1999]. However, we have only detected a unique transcript for chicken annexin A5; moreover, the analysis of its gene revealed only one promoter and the absence of TATA boxes and other cis-regulatory elements [Pfannmu È ller et al, 1993;Ferna Ândez et al, 1994], suggesting that the annexin A5 gene might be more related to that of a housekeeping gene. Here we show for the ®rst time that at least two regulatory mechanisms exist which control annexin A5 expression in a developmental and an environmentally regulated manner.…”
Section: Discussionmentioning
confidence: 73%
“…However, it reappears in the calci®cation zone of hypertrophic cartilage, both in hypertrophic chondrocytes and in osteoblasts as detected by in situ hybridization and by immunohistochemistry [Hofmann et al, 1992;Kirsch et al, 1997]. We have previously reported on the structure of the chicken annexin A5 gene and shown that the promoter region lacks the typical TATA-box but contains a GCrich region, with multiple Sp1 sites typical of housekeeping genes which may possibly promote transcription from several start sites [Pfannmu È ller et al, 1993]. Little is still known, however, on the regulatory mechanisms of annexin gene expression and on its regulation by growth stimuli, such as the c-fos protooncogene [Braselmann et al, 1992], cell differentiation degree [Hofmann et al, 1992;Kirsch et al, 1997], or even in cartilage diseases such as osteoarthritis [Mollenhauer et al, 1999;Kirsch et al, 2000b].…”
mentioning
confidence: 93%
“…Preliminary evidence was presented for tissue-specific differences of annexins from chondrocytes, bone cells, fibroblasts or other tissues [5]. The analysis of the annexin V gene, however, provided no evidence for more than one annexin V gene, splice variants or isoforms [6,7].…”
Section: Anchorin CII a Collagen-binding Protein Of The Annexin Familymentioning
confidence: 99%
“…Preliminary evidence was presented for tissue-specific differences of annexins from chondrocytes, bone cells, fibroblasts or other tissues [5]. The analysis of the annexin V gene, however, provided no evidence for more than one annexin V gene, splice variants or isoforms [6,7].The concept of anchorin CII as a collagen-receptor of chondrocyte membranes was consistent with its localization on the chondrocyte surface by immunofluorescence [2]. This was questioned, however, when the analysis of the protein structure [8] revealed homology to calpactin I and lipocortin II, and thus documented the absence of a hydrophobic signal peptide and transmembrane sequences.…”
mentioning
confidence: 99%
“…(13) Briefly, a full-length chicken annexin II, chicken annexin V, and human annexin VI complementary DNA (cDNA) clones were subcloned into the pGEX expression vector. (29)(30)(31) Recombinant annexin II, V, and VI glutathione S-transferase (GST) fusion proteins were expressed in Escherichia coli DH5␣FЈ and purified. The fusion proteins were subjected to PreScission protease (Pharmacia, Piscataway, NJ, USA) cleavage to release the annexin molecules from the GST moiety.…”
Section: Recombinant Annexin II V and Vi Moleculesmentioning
confidence: 99%